2007
DOI: 10.1177/0310057x0703500311
|View full text |Cite
|
Sign up to set email alerts
|

Critical Incidents in a Multidisciplinary Intensive Care Unit

Abstract: We aimed to determine the type and frequency of critical incidents in a multidisciplinary intensive care unit, to determine outcomes consequent to these incidents and to devise corrective strategies. Prospectively collected data on critical incidents during a 33-month period were analysed. In all, 1918 patients were admitted to the unit during the study period. Each incident was analysed in detail. A system-based corrective strategy was sought for and implemented as appropriate. In these patients, 280 critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…Hay un imperativo profesional y ético que obliga a reconocer estas situaciones y reducir su incidencia e importancia. Esto es especialmente importante en la Medicina Crítica y de Emergencias donde la similitud con sectores de alto riesgo (energía nuclear, aeronáutica, petroquímica) es mayor 22,23 , se es más proclive al error y su importancia puede ser de mayor impacto 17,24,25 .…”
Section: Discussionunclassified
“…Hay un imperativo profesional y ético que obliga a reconocer estas situaciones y reducir su incidencia e importancia. Esto es especialmente importante en la Medicina Crítica y de Emergencias donde la similitud con sectores de alto riesgo (energía nuclear, aeronáutica, petroquímica) es mayor 22,23 , se es más proclive al error y su importancia puede ser de mayor impacto 17,24,25 .…”
Section: Discussionunclassified
“…This study is a pretest and post-test intervention case-control study and the statistical community of this research includes the nurses and specialist physicians working in intensive care unit (ICU1, CCU2, mental unit, burn wards, pediatric ICU and hemodialysis wards) of Beheshti Hospital and Emam Sajad hospitals in Yasouj and Shahid Rajae Gachsaran and Emam Khomeini Dehdasht in Iran in 2010. Sample admission requirements included the lack of any severe depression or anxiety disorders as well as work experience of more than 2 years in intensive care units.…”
Section: Methodsmentioning
confidence: 99%
“…This stress is tangible in intensive care and internal units. These environments can be potentially stressful and require stress-related interventions 25. Emotional intelligence has been described as an argued ability, capacity, and skill of understanding oneself and others, assessing and managing the emotions of oneself and the others, and a group of people with whom we are associated 6.…”
Section: Introductionmentioning
confidence: 99%
“…There are observational data suggesting that transport of patients outside the ICU setting may carry increased risk: one study found that 43% of medical errors in ICU patients occurred when they were outside the ICU [55], and the incidence of adverse events and critical events in patients undergoing intrahospital transport [54,56,57] is consistently higher than the incident rate of adverse events documented in the ICU [58,59]. There are no comparative studies, however, evaluating outcomes or adverse event rates in patients who are either transported or not transported.…”
Section: Con – Risks Of Transport and Impact On Transferring Hospitalmentioning
confidence: 99%